The Effects of Price Regulation on Pharmaceutical Expenditure and Availability - Mika Kortelainen; Jaakko Markkanen; Markku Siikanen; Otto Toivanen (Helsinki Graduate School of Economics, 2023)
Quasi-experimental evidence on the effectiveness of price regulation policies in curbing pharmaceutical expenditure is scarce. We analyze widely utilized generic substitution and reference price policies using data from the Nordic countries. Constructing treatment and control groups by matching data across countries by active ingredients and employing difference-in-difference methods on market-level observations, we find that expenditure per dose decreases by 40% moving from the laxest to the strictest regime. Prices decrease less: Reallocation of demand to cheaper products likely explains the difference. We find no adverse effects on pharmaceutical availability and non-existent or positive quantity effects.
Keywords: I11; I18; H51; L51; L65; C23; 330; pharmaceutical expenditure; pharmaceutical pricing; generic competition; reference pricing; regulation